Changes in gut microbiota composition after 12 weeks of a home-based lifestyle intervention in breast cancer survivors during the COVID-19 lockdown - Donati Zeppa, Sabrina; Natalucci, Valentina; Agostini, Deborah; Vallorani, Luciana; Amatori, Stefano; Sisti, Davide; Rocchi, Marco B. L.; Pazienza, Valerio; Perri, Francesco; Villani, Annacandida; Binda, Elena; Panebianco, Concetta; et al. (Frontiers in Oncology, 2023)
Background: Breast cancer (BC) is the second-leading cause of cancer-related death worldwide. This study aimed to investigate the effects of a 12-week home-based lifestyle intervention (based on nutrition and exercise) on gut microbial composition in twenty BC survivors of the MoviS clinical trial (protocol: NCT 04818359). Methods: Gut microbiota analysis through 16S rRNA gene sequencing, anthropometrics, Mediterranean diet (MD) adherence, and cardiometabolic parameters were evaluated before (T0) and after (T1) the lifestyle intervention (LI). Results: Beneficial effects of the LI were observed on MD adherence, MeDiet score and cardiometabolic parameters (T0 vs T1). A robust reduction of Proteobacteria was observed after LI, which is able to reshape the gut microbiota by modulating microorganisms capable of decreasing inflammation and others involved in improving the lipid and glycemic assets of the host. A significant negative correlation between fasting glucose and Clostridia_vadinBB60 (r = -0.62), insulin and homeostatic model assessment (HOMA) index and Butyricicoccus genera (r = -0.72 and -0.66, respectively), and HDL cholesterol and Escherichia/Shigella (r = -0.59) have been reported. Moreover, positive correlations were found between MD adherence and Lachnospiraceae_ND3007 (r = 0.50), Faecalibacterium (r = 0.38) and Butyricimonas (r = 0.39). Conclusion: These data suggest that adopting a healthy lifestyle, may contribute to ameliorate several biological parameters that could be involved in the prevention of cancer relapses through the modulation of gut microbiota.